Deodorisation of fish oil by nanofiltration membrane process: focus on volatile flavour compounds and fatty acids composition. (6th November 2017) - Fang, Yizhou; Gu, Saiqi; Zhang, Jianyou; Liu, Shulai; Ding, Yuting; Liu, Jianhua
Summary: This study focuses on the investigations for the deodorisation of tuna oil and squid oil through n‐hexane extraction and nanofiltration membrane process with a molecular weight cut‐off of 360 Da. The change of the odour and the fatty acids composition were analysed. Volatile components analysed by monolithic material sorptive extraction (MMSE) combined with gas chromatography–mass spectrometry (GC‐MS) suggested that nanofiltration membrane process could remove the majority of the volatile components, and the removal rate was approximate to 80%. The odour activity values (OAVs) of the volatile components in tuna oil and squid oil were significantly reduced from 125.23 to 17.47 and 129.76 to 10.06 ( P < 0.05), respectively. On the other hand, the contents of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) were increased as expected. These results indicated that the organic solvent nanofiltration technique had obvious effects on deodorisation of fish oil, and it would be a promising deodorisation method in fish oil refining industry. Abstract : Fish oil deodorization by nanofiltration membrane.